Skill and qualification: the contribution of NVQs to raising skill levels - Grugulis, I (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2002)
This paper is an evaluation of the British system of National Vocational Qualifications (NVQs) which focuses specifically on their capacity to increase the skill levels of the working population. It reviews the way that NVQs were designed and developed and argues that they are ill-equipped to encourage knowledge and skills, partly because they simply replicate the weaknesses which currently exist in the labour market and partly because of the qualifications' own focus on observed workplace behaviours. NVQs were intended to be 'employer-led' and the assumptions which underpin their design are unitarist. In contrast, the German apprenticeship system is developed and implemented by pluralist consortia of employers, trade unions, educationalists and regional governments. The qualifications which result are far better equipped to support skill levels than are NVQs.